1964
DOI: 10.1149/1.2425978
|View full text |Cite
|
Sign up to set email alerts
|

The Transmission of Electrolytically Deposited Hydrogen through a Palladium Membrane Electrode

Abstract: Hydrogen is deposited eleetrolytically on one side (the entrance side) of a palladium membrane at a rate --i(amp/cm2). The amount of hydrogen transmitted is measured by noting the change in normality of a solution of a strong oxidizing agent, e.g., Ce +4 or S2Os =, on the other side (the exit side),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1964
1964
1992
1992

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The fact that the reaction is first order with respect to the titanium (IV) is in agreement with other studies on different oxidizing agents (5,6,9). In these studies the first order kinetics was attributed to a diffusion limited process.…”
Section: Results and Discussion Of Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that the reaction is first order with respect to the titanium (IV) is in agreement with other studies on different oxidizing agents (5,6,9). In these studies the first order kinetics was attributed to a diffusion limited process.…”
Section: Results and Discussion Of Resultssupporting
confidence: 91%
“…Castellan (9) has studied the reaction of cerium (IV) with hydrogen diffusing through palladium membranes. In most of the studies with oxidizing agents, it was concluded that the rate-determining step was the diffusion of the oxidizing agent to the hydrided surface (6,9). If this is the rate-determining step, the addition of poisons should have no effect on the rate of the reaction; therefore, a study was initiated to determine whether poisons did affect the rate of reduction of titanium(IV) by hydrogen diffusing through a palladium membrane.…”
mentioning
confidence: 99%
“…According to the literature (13)(14)(15)(16), dissolved oxidants (including oxygen) also result in inaccurate pH and reference electrode potentials due to depolarization of the palladium hydride electrode. It is shown beIow that electrode lifetimes of the order of 1-2 weeks can be obtained by proper selection of the electrode volume and surface to volume ratio, even in the presence of dissolved oxygen.…”
Section: Electrodesmentioning
confidence: 99%
“…The investigations reported in Parts I and II, (1,2), show that it is necessary to measure the rate of transmission of hydrogen as a function of the hydrogen pressure on the exit side of the membrane to obtain a more complete characterization of the mechanism. In this paper, the dependence of the rate of transmission on pressure and temperature as well as on membrane thickness is described.…”
mentioning
confidence: 99%